(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The rise in non-performing assets (NPAs) in the Indian banking system threatens not only profitability but also economic growth prospects. This growth in NPAs needs more provisioning, diverting earnings to bad loans and worsening the problem. NPAs have a negative impact on the Micro, Small and Medium Enterprises (MSME)sector in particular, resulting in limited access to loans, slowed growth, and reduced financial stability. Non-performing assets (NPAs) must be managed effectively in the MSME sector to ensure liquidity and profitability. Despite this pressing need, the potential for using AI to address NPA-related concerns in financial institutions is unexplored. AI has the potential to detect gaps in financial products and optimize operational procedures, ultimately providing a solution to the problem at hand. However, the use of AI to reduce NPAs in the context of sustainable financial institutions has received little consideration in recent research. This study seeks to close this gap by investigating the influence of an AI powered credit assessment system on NPAs in the MSME sector and financial institutions. By addressing the important issue of rising NPAs in the Indian banking industry, this study aims to shed light on AI's revolutionary potential in fostering financial stability and sustainability.